Transformation of Islamic Religious Education Through the Independent Curriculum - Shidiq Agung Sutrisno; Sukiman; Zainal Arifin; Maragustam (Universitas Pendidikan Ganesha, 2026)
The implementation of the Merdeka Curriculum in Islamic boarding schools still faces challenges in integrating traditional values with modern educational innovations. In addition, the limited understanding of the innovation diffusion process has resulted in curriculum implementation that is not yet fully effective and contextual. This study aims to analyze, evaluate, and interpret the implementation of the Merdeka Curriculum and its contribution to improving the quality of Islamic Religious Education. This research employs a qualitative approach with a descriptive case study design. The research subjects include boarding school leaders, teachers, students, parents, and the surrounding community, with participants selected purposively. Data were collected through in-depth interviews, participatory observation, and documentation studies using interview guidelines and observation sheets as instruments. Data analysis was conducted using the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. The findings indicate that the integration of the Merdeka Curriculum with the national curriculum and pesantren traditions has been effectively implemented, enhancing the relevance of learning and the development of students’ competencies. The study concludes that the success of curriculum implementation is influenced by value alignment, leadership, and adaptive innovation strategies. The implications of this study highlight the importance of contextual and collaborative approaches in curriculum development within Islamic educational institutions.